(untitled) (Research, Society and Development, 2020)
This article aims to present diversity as an advantage for companies, not only in the sense of fulfilling a duty of social responsibility, but mainly because the formation of a diverse and talented team of employees, in a work environment devoid of prejudice and discrimination will certainly result in satisfactory results for the corporate body. For this, the methodology is based on the bibliographic procedure, with data collection from various areas, making the nature of the research qualitative. The Universal Declaration of Human Rights has a very important role in this scenario, in terms of protecting and safeguarding the well-being of the oppressed, in whatever environment. In this sense, it is up to companies to adopt policies of diversity and social inclusion, to ensure the effectiveness in recruiting more creative professionals who use a more diversified way of working, expanding knowledge, skills and intercultural understanding.